Study of solar driven silica gel-water based adsorption chiller - Habib, K. (Institute of Physics Publishing, 2015)
In this study, a dynamic behaviour of a solar powered single stage four bed adsorption chiller has been analysed designed for Malaysian climate. Silica gel and water have been used as adsorbent-refrigerant pair. A simulation program has been developed for modeling and performance evaluation of the chiller using the meteorological data of Kuala Lumpur. The optimum cooling capacity and coefficient of performance (COP) are calculated in terms of adsorption/desorption cycle time and regeneration temperature. Results indicate that the chiller is feasible even when low temperature heat source is available. Results also show that the adsorption cycle can achieve a cooling capacity of 14 kW when the heat source temperature is about 85Â°C.